Alternative Models of State-Religion Relations in Western Countries and the Case of Turkey - (:unkn) unknown (My University, 2015)
Batı ülkeleri 1980'lerden itibaren dinlerin kamusal taleplerinin arttığı bir sürece tanık olmaktadır. Post-seküler toplum tartışmalarının sürdüğü bir ortamda, dini talepler karşısında sessiz kalamayan Batı ülkeleri din-devlet ilişkilerini gözden geçirmeye yönelmişlerdir. Post-komünist süreci yaşayan ülkeler gibi katı bir laikliği benimseyen Fransa da son dönemlerde din-devlet ilişkilerinde yumuşama sayılabilecek adımlar atmıştır. Yine din ve devletin kesin bir ayrımına sahip olan ABD'de din-devlet arasındaki ayrım duvarıyla ilgili tartışmalara yol açan gelişmeler gözlenmektedir. Öncelikle Batı ülkelerindeki değişime dikkat çeken makale, din-devlet arasında katı ayrım gözeten modellerin uyuşmacı modele doğru evrildiği görüşünü çeşitli örneklerle açıklamaktadır. Makale ayrıca Türkiye'nin geçmişten bugüne din-devlet ilişkilerinde aldığı tutumları değerlendirirken son dönemde devletin dinle daha uyumlu bir ilişki biçimi sergilediğini belirtmekte ve bu durumun Batı ülkelerindeki seyirle uyumlu olduğu görüşünü ortaya koymaktadır

Beginning with the 1980s, Western countries have been witnessing a process in which public demands of religions are on the increase. At a time when debates about postsecular society were going on, these countries could not remain indifferent to religious demands and moved to reconsider religion-state relations. Just like the post-communist states, France, which had adopted a rigid version of secularism, also took steps recently that can be interpreted as the relaxation of religion-state relations. Again, we see developments in the U.S., where an absolute separation of church and state exists, that lead to debates on where to draw the line that separates the state and church. Drawing attention principally to the ongoing change in Western countries, the article expounds through various examples of how the models that envisage a rigid separation of religion and state are evolving into the reconciliatory model. While reviewing the attitudes toward religion-state relations in Turkey from past to present, the article also holds that the state has developed a more harmonious relationship with religion lately and that this situation is in tune with the process in Western countries
lternative Models of State-Religion Relations in Western Countries and the Case of Turkey
Keywords: Kültürel Çalışmalar; Tarih; Siyasi Bilimler; Kamu Yönetimi